2019
DOI: 10.1001/jamasurg.2019.2875
|View full text |Cite
|
Sign up to set email alerts
|

Association of Decreased Postsurgical Opioid Prescribing With Patients’ Satisfaction With Surgeons

Abstract: IMPORTANCE Opioid overdose is the leading cause of injury-related death in the United States. Several studies have shown that surgeons overprescribe opioids, and guidelines for appropriate opioid prescribing are available. Concern about patient-reported satisfaction scores may be a barrier to surgeons adopting guideline-directed prescribing.OBJECTIVE To determine whether decreased opioid prescribing is associated with a decrease in patient-reported satisfaction with their surgeon. DESIGN, SETTING, AND PARTICIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 20 publications
2
27
2
Order By: Relevance
“…Previous research has suggested that one obstacle to the widespread implementation of decreased opioidprescribing protocols is concern that narcotic reduction may lead to lower patient satisfaction scores. 13 These satisfaction metrics are important for health care center valuations but also have the ability to influence the care-providing, itself. Merriman et al 3 recently published the results of a survey sent to emergency medicine physicians and reported that 50% of physicians believe patients are more satisfied when given opioid medications in the emergency department or as a discharge prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that one obstacle to the widespread implementation of decreased opioidprescribing protocols is concern that narcotic reduction may lead to lower patient satisfaction scores. 13 These satisfaction metrics are important for health care center valuations but also have the ability to influence the care-providing, itself. Merriman et al 3 recently published the results of a survey sent to emergency medicine physicians and reported that 50% of physicians believe patients are more satisfied when given opioid medications in the emergency department or as a discharge prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed no statistically significant difference in patient satisfaction scores after decreasing the number of postoperative opioid pills prescribed by more than half following mastectomy, inguinal hernia repair, or cholecystectomy. 11…”
Section: Discussionmentioning
confidence: 99%
“…Despite these policy changes, the assumption that receipt of opioids during hospitalization improves patient care experiences has not been thoroughly tested. First, studies focusing on surgical inpatients reported inconsistent findings between receipt of opioids and patient experiences of care 15‐19 . For instance, some of the studies found that higher HCAHPS scores (ie, better patient experiences) were associated with less, not more, opioid use 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some of the studies found that higher HCAHPS scores (ie, better patient experiences) were associated with less, not more, opioid use 18,19 . Other studies reported a lack of association between receipt of opioids and surgical patients’ experiences with care 15,17,20 . Second, prior studies focused on surgical inpatients failed to account for potential bias resulting from confounding by indication, which is the possibility that individuals receiving opioids differ meaningfully from patients who do not.…”
Section: Introductionmentioning
confidence: 99%